Penerapan bahan ajar berbantuan ispring suite pada materi bentuk aljabar terhadap kemampuan pemahaman matematis siswa kelas VII - Andita Aulia Sofiah; Siti Chotimah; Heris Hendriana (IKIP Siliwangi, 2023)
The purpose of this research is to determine whether there is a difference between the average mathematical understanding of students who use iSpring Suite-assisted teaching materials and the average mathematical understanding of students who use iSpring Suite-assisted teaching materials. Comparative quantitative research (comparison) was used to establish this type of research. The population of this study were students of class VII SMP Negeri 1 Parongpong. Data analysis was performed using a two-tailed t-test with conditions of normality and homogeneity tests. The normality test shows that ð»ð‘œ is accepted, then the homogeneity test shows an average of 0.106 and a median of 0.729. The results showed that there was a difference in the average understanding of mathematics between students who used iSpring Suite-assisted teaching materials and those who did not. The one-tailed t test shows that the average mathematical understanding of students who use iSpring Suite assisted teaching materials is better than the average mathematical understanding of students who do not use iSpring Suite assisted teaching materials.